PENINGKATAN PENGETAHUAN TENAGA DAN KADER KESEHATAN SEBAGAI KUNCI PENCEGAHAN INFEKSI SISTEM SARAF PUSAT PADA ANAK DI KABUPATEN SUMENEP - Prastiya Indra Gunawan; Riza Noviandi; Sunny Mariana Samosir; Dwiyanti Puspitasari (Universitas Mataram, 2023)
Central nervous system (CNS) infection is a major cause of morbidity and mortality in children. The causes of CNS infections that are often found in children include bacteria, viruses, fungi, and parasites. Immunization is one way that has been proven safe and effective in preventing CNS infections in children. However, the coverage of child protection in Sumenep Regency still has not reached the target. The purpose of this community service activity is to increase the knowledge of health workers and cadres in the Pasongsongan Health Center area, Sumenep Regency about the dangers of CNS infections in children and their prevention. The selected partners are the Pasongsongan Community Health Center which covers the working area of 10 villages in Pasongsongan District, Sumenep Regency. Activities carried out using the counseling method through media zoom, in the form of lectures and questions and answers about the introduction and prevention of CNS infections. Pre-test and post-test assessments of extension activities were carried out to assess the increase in the participants' level of knowledge. There were 72 participants with varied backgrounds consisting of doctors, nurses, midwives, health workers and health cadres. As many as 68% of health workers had received socialization about CNS infection in children before during their education or continuing medical education. The level of knowledge of the participants was assessed from the pre and post tests which consisted of 10 multiple choice questions on the topic of CNS infection in children. From the evaluation results, the average pre-test score was 68.4 and the post-test was 100. An increase in knowledge was obtained with an average increase of 36.48% with the highest increase of 70 points and the smallest increase of 10 points. Community service activities in the form of counseling on CNS infections in children can increase the knowledge of health workers and cadres in the Pasongsongan Health Center, Sumenep Regency, about children's SSP infections.